Internationalization in the airline industry: econometric relations among business models, brand, alliances, and institutions - Almeida, Eric Felipe Schneider de (2020)
Air transport firms are characterized by their network nature and market expansion through connecting different economic locations, e.g. cities and countries. From a new institutional economics perspective - which provides a comprehensive framework in analyzing network infrastructures such as air transport industry - airline internationalization phenomena have been little explored. Through a quantitative investigation, this text seeks a broader understanding of existent relations among business models, brand, strategic alliances and institutions that may impact management decisions on airline internationalization. By choosing decision rights sharing via an organizational form (membership in airline alliance) and a property right (brand licensing) as internationalization criteria, an econometric model has been developed to account for different institutional environments against different airline modes of operation. Some conclusions were drawn about how companies strategically develop their internationalization process. Regarding special test variables, brand internationalization and alliance membership are negatively correlated within this internationalization scope, especially in the case of low cost carriers, steering to a discussion about modes of entry chosen by carriers according to the institutional \"openness\" given by countries and strategies of resources allocation of each airline sampled.